A primary rat neuron-astrocyte-microglia tri-culture model for studying mechanisms of neurotoxicity - Badley, Jessie R.; Bhusal, Aishwarya; Lein, Pamela J. (Frontiers in Toxicology, 2025)
Primary cell cultures from rodent brain are widely used to investigate molecular and cellular mechanisms of neurotoxicity. To date, however, it has been challenging to reliably culture endogenous microglia in dissociated mixed cultures. This is a significant limitation of most in vitro neural cell models given the growing awareness of the importance of interactions between neurons, astrocytes and microglia in defining responses to neurotoxic exposures. We recently developed a tri-culture model consisting of neurons, astrocytes and microglia dissociated from the developing rat neocortex and demonstrated that this tri-culture model more faithfully mimics in vivo neuroinflammatory responses then standard neuron-only or neuron-astrocyte co-cultures. Here, we describe our protocol for generating tri-cultures of rat cortical neurons, astrocytes and microglia in which all 3 cell types can be maintained for up to 1 month in culture at the same relative ratio observed in the developing rat neocortex. We also discuss applications of this model for neurotoxicity testing, as well as the potential of this model to fill a current gap for assessing neuroinflammation in the in vitro testing battery for developmental neurotoxicity.